Politics, property, and production in the West African Sahel : understanding natural resources management - Benjaminsen, Tor Arve.; Lund, Christian (Uppsala : Nordiska Afrikainstitutet, 2001)
Through a number of case studies from the West African Sahel, this book links and explores natural resources management from the perspectives of politics, property and production.
Keywords: Environmental management; Environmental management -- Political aspects; Land tenure